(untitled) (Advances in Knowledge Representation, 2021)
Of all the artificial intelligence technologies, ontologies are the most dependent on human expertise and classification skills. The methodologies for building ontologies share a stage that requires the use of an ontology editor for formalizing knowledge. For students in information science. The use of such editors is still an obstacle, since the information science curriculum does not cover the skills required for ontology development. To bridge this gap, we have developed Onto4AllEditor, a web-based graphic ontology editor, with the aim of providing resources for the creation of lightweight ontologies. Onto4AllEditor aims also to foster ontologies within Information Science.